Public and Private Schools Acquire and use Teaching and Learning Materials (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The research delves into the influence of gender on learning outcomes and the role of teacher training in shaping these results. Through a methodical analysis and comparison, the thesis provides insights into the effectiveness of educational strategies and their implications for enhancing student achievement. The findings are intended to inform educators, policymakers, and stakeholders in making evidence-based decisions to improve educational practices and bridge the gap between government and private schooling systems.